A game theory perspective of asymmetric alliances for new product development. (10th April 2015) - Chou, P. Ben; Thomas, Ellen
By adopting and extending the game theoretical model developed by Chou (2011) from symmetric firms to asymmetric firms with monetary transfers, we characterise the strategic interactions between asymmetric firms in an alliance for new product development. We also integrate the game theoretical literature and empirical studies to show that a broader–scope link alliance tends to benefit the larger firm, while a narrower–scope scale alliance tends to benefit the smaller firm. The asymmetry of benefits also enables the larger firm to subsidise the smaller firm to maintain the stability of the alliance if it is beneficial for the larger firm to do so.